Polarization Conflicts and Stakeholders Interests in Tin Mining Industry Policies in Bangka Belitung Islands Province, Indonesia between 2000 and 2019 - Darol Arkum; Shulby Yozar Ariadhy; Bambang Ari Satria (Conference Series, 2020)
Bangka Belitung Islands Province is the second largest tin producer that has been widely known in the international market. It has been exploited since the 18th century. In the New Order era, tin mining was exploited by two large companies, namely PT. Timah, Indonesia Tbk and PT. Koba Tin, Malaysia. The purpose of this study was to analyze the polarization of conflicts and stakeholders interests in tin mining policies in Bangka Belitung Islands Province between 2000 and 2019. This study used a qualitative approach with phenomenological analysis techniques. Data collection was carried out by conducting interviews with key informants, Focus Group Discussion, with 30 supervisors, in-depth interviews, and documentation. This study concluded that the polarization of various interest groups in tin mining policies is related to how the stakeholders in the policy reacted to the direct and indirect impact of certain policies to their values ??and interests. The implication of this research is that the central government must consider the stakeholders relationship interests in formulating mining policies and implementation.